Pengembangan E-Modul Pada Mata Pelajaran Pekerjaan Dasar Teknik Otomotif - hanif ramdani; Nurcholish Arifin Handoyono; Sigit Purnomo (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2022)
This research aimed for (1) obtaining good and quality E-Modul for The Basic Work of Automotive Engineering Subject in the Occupational Health and Safety material at SMK Muhammadiyah Piyungan, (2) knowing the appropriateness of the E-Modul for The Basic Work of Automotive Engineering Subject in the Occupational Health and Safety material at SMK Muhammadiyah Piyungan. The type of this study is a research and development by using 4D model. The subject of this study consists of material expert namely the Teacher of SMK Muhammadiyah Piyungan and media expert namely the Lecturer of Mechanical Engineering Vocational Education Study Program of UST Yogyakarta, along the students of class 10 of light vehicles engineering department as the user from the developed instructional media. The object of this study is the E- Modul for The Basic Work of Automotive Engineering Subject in the Occupational Health and Safety material. Data collection technique uses questionnaire and observation and data collection instrument uses preliminary study, instrument, and expert validation instrumen as well as product trials.The data analysis technique uses quantitative descriptive. This research and decelopment model consists of few stages such as define, design, development, and dissemination. The result of this study.were the instructional media in a form of E-Modul for The Basic Work of Automotive Engineering Subject in the Occupational Health andlSafety material. The instructional media development was proper to be used according to the feasibility test by the material expert in the amount of 3,00, by the media expert was 3,16, and the field test by 3,08, so therefore the evaluation result by the material expert, media expert, and field test obtained the average score by 3,08 out of the 4 as maximal score. According to the result obtained from feasibility test, the E-Modullof the Occupational Health and Safety was proper to use in the learning.